2012
DOI: 10.6004/jnccn.2012.0062
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Patients With Stage IIIA Non–Small Cell Lung Cancer With N2 Mediastinal Node Involvement

Abstract: Patients with stage IIIA non-small cell lung cancer, determined based on involvement of ipsilateral mediastinal lymph nodes, represent the most challenging management problem in this disease. Patients with this stage disease may have very different degrees of lymph node involvement. The pathologic confirmation of this involvement is a key step in the therapeutic decision. The difference in the degree of lymph node compromise has prognostic and treatment implications. Based on multiple considerations, patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 63 publications
0
74
2
1
Order By: Relevance
“…Multimodality treatment was planned for all patients, and all of them received adjuvant chemotherapy except for 8 patients who did not receive postoperative treatment because they died or showed a poor postoperative performance status. Surprisingly, our median 3-and 5-year survival rates for patients diagnosed as N2a1 were considerably better than those reported for N2 patients treated with neoadjuvant therapy and surgery [14,16]. Similarly, a recent French report [11] on 871 patients advocated for a better stratification of IIIA-N2 NSCLC, because they found a significant difference in OS according to the number and position of the lymph node stations involved.…”
Section: Discussioncontrasting
confidence: 51%
“…Multimodality treatment was planned for all patients, and all of them received adjuvant chemotherapy except for 8 patients who did not receive postoperative treatment because they died or showed a poor postoperative performance status. Surprisingly, our median 3-and 5-year survival rates for patients diagnosed as N2a1 were considerably better than those reported for N2 patients treated with neoadjuvant therapy and surgery [14,16]. Similarly, a recent French report [11] on 871 patients advocated for a better stratification of IIIA-N2 NSCLC, because they found a significant difference in OS according to the number and position of the lymph node stations involved.…”
Section: Discussioncontrasting
confidence: 51%
“…In North America, surgical treatment for cN2 disease is generally reserved after induction therapy, given these considerations: (1) patients with N2 disease are more likely to experience systemic failure, (2) patients are more likely to receive full-dose and full-cycle chemotherapy when those are given preoperatively relative to adjuvant delivery, and (3) induction chemotherapy provides an assessment of tumor biology and treatment response. This approach is supported by the National Comprehensive Cancer Center guidelines and by other groups [14][15][16].…”
Section: N2 Seen From Different Anglesmentioning
confidence: 99%
“…These findings suggest that the majority of lower lobe tumors with multiple mediastinal station metastases, including superior mediastinal nodes, would not have been candidates for trimodality therapy in the study conducted by Kamel et al Indeed, it has been reported that most institutions (90.5%) that belong to the National Comprehensive Cancer Network in the USA consider surgery in patients with a single lymph node station smaller than 3 cm, while 47.6% of the institutions consider surgery in patients with multiple station involvement (as long as no lymph node is larger than 3 cm), and some institutions (16.7%) consider surgery in patients with multiple stations even if the lymph node is larger than 3 cm (13). The 2013 American College of Chest Physicians (ACCP) guideline categorized the resectability of tumors based on these cN2 statuses, such as infiltrative or discrete nodes type, and recommendations for treatment were made according to the cN2 status (14).…”
mentioning
confidence: 99%